Hubungan Pencapaian Tugas Perkembangan Keluarga Tahap VIII (Aging Family) dengan Perilaku Pemenuhan Kebutuhan Spiritual: Sholat Pada Lansia - Fajar Kharisma; Hanny Rasni; Retno Purwandari (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Not all religious activity in the elderly can be implemented well, so there are limitations due to physicalconditions that are not strong anymore. Therefore, the family is expected to motivate and facilitate theelderly to meet the spiritual needs so as to increase devotion elderly against God Almighty. This researchaims to analyze the relationship between eight stage (aging family) of family development task with thebehavior of spiritual fulfillment: sholat on the elderly in the Sumbersari village, Jember regency. Thisresearch was observasional analytic using cross sectional study. Data collection was conducted inDecember 2017 at 82 elderly by using cluster random sampling. The research result showed that Familydevelopment task is reached (56.1%) and the average behavior of spiritual fulfillment: prayers 69.11.Statistical test used the Spearman rank that indicated p-value>alpha with 0.359>0.05 which meant therewas no relation between eight stage (aging family) of family development task with the behavior ofspiritual fulfillment: prayers on the elderly in the Sumbersari village, Jember regency. Family support isvery important for the elderly, especially in carrying out the task the development of families with elderly.However, the research result obtained family development task not have correlation on the behavior ofspiritual fulfillment: sholat in elderly, it can be affected by other factors such as the elderly haveconfidence and awareness in carrying out religion activities such as sholat for the provision in the afterlife. Keywords: aging family, sholat, elderly